Sexual Harassment: M. Hasbi Ash-Shiddieqy's Perspective in the Interpretation of An-Nur - Zubaidi, Nadya Rahma; Zainuddin, Ahmad; Mashuri, M. Mukhid; Mufid, Miftarah Ainul (Literacy: Journal of Education and Social Science, 2024)
This article was created based on the many cases of sexual harassment in Indonesia, This phenomenon covers various forms of sexual violence, ranging from verbal to physical harassment, which occur in various environments. The Qur'an is the ultimate guide for Muslims in organizing their lives and dealing with various problems. The Qur'an was revealed with the aim of becoming a guideline for life, which can bring blessings to this world and the hereafter. Sexual Harassment can be called fahsya' which has meaning in everything that is considered bad by him, both in words and actions. The word